2021
DOI: 10.31933/dijemss.v2i3.762
|View full text |Cite
|
Sign up to set email alerts
|

The Model of Patient Satisfaction and Trust: A Study at BPJS Patient

Abstract: Health is a major requirement for every resident living in this world, and health development essentially concerns both physical and mental health. The state of health of a person will be influential on the aspects of social life is economic, and the continuity of the life of a nation and a country anywhere in the world, both in countries that have developed and in developing countries such as Indonesia as well as health is a right and an investment for all citizens of Indonesia. The research method uses descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…We found that a higher level of satisfaction with insurance by patients increased the trust in insurance programs. Recent studies [68][69][70] also proved that increase in patient satisfaction could have a positive impact on patients' trust. Another SEM research on URRBMI enrollees suggested that the perception of policy quality was a decisive factor in the perceived quality of URRBMI [20].…”
Section: Discussionmentioning
confidence: 99%
“…We found that a higher level of satisfaction with insurance by patients increased the trust in insurance programs. Recent studies [68][69][70] also proved that increase in patient satisfaction could have a positive impact on patients' trust. Another SEM research on URRBMI enrollees suggested that the perception of policy quality was a decisive factor in the perceived quality of URRBMI [20].…”
Section: Discussionmentioning
confidence: 99%
“…Based on Cahyati (2021), the results of the study can be seen that there is a degree of variable contribution of service provision to patient trust through patient satisfaction. The better the delivery of services provided by Puskesmas Purbaratu Kota Tasikmalaya, the better the patient satisfaction received, which in turn will have an impact on increasing patient trust in Puskesmas Purbaratu Kota Tasikmalaya.…”
Section: Resultsmentioning
confidence: 99%
“…and the readiness of the Indonesian people. So the government must strive for the health sector as well as possible, providing adequate health services and easily accessible to the general public (Cahyati, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian Endartiwi (2020) juga menunjukkan Indeks kepuasan masyarakat terhadap pelayanan rawat jalan peserta BPJS Kesehatan di Puskesmas Penelitian Tome et al, (2019) menunjukkan ada hubungan antara kehandalan, daya tanggap, jaminan, empati, dan bukti fisik terhadap kepuasan pasien Jaminan Kesehatan Nasional. Semakin baik pemberian layanan yang diberikan oleh kesehatan pusat Purbaratu Kota Tasikmalaya semakin baik kepuasan yang diterima pasien yang akan pada akhirnya berdampak pada meningkatnya kepercayaan pasien terhadap puskesmas Purbaratu Kota Tasikmalaya (Cahyati, 2021).…”
Section: Pembahasanunclassified